Kartvelological Studies in Poland: 1920-2011 - Fr. Henryk Paprocki (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The present paper is a general review of the development of Karvelology in Poland. However, this topic cannot obviously be exphansted in a short article. Since the compilation of a bibliography of works connected with Georgia has not been completed yet, further long-term work is needed to study Kartvelological research here. Nevertheless, I should try focus attention on the main issue by describing the basic stages of Kartvelological studies in Poland.